A Map of Consciousness Studies: Questions and Approaches - Niikawa, Takuya (Frontiers in Psychology, 2020)
This article aims to present a map of consciousness studies, which consists of a list of fundamental questions about consciousness and existing approaches to them. The question list includes five fundamental categories: Definitional, Phenomenological, Epistemological, Ontological, and Axiological. Each fundamental category is divided into more determinate questions. Existing approaches to each question are also classified into a few groups, presenting principal researchers who take each kind of approach. In the final section, I demonstrate the usefulness of the proposed map of consciousness studies by applying it to examine the integrated information theory and the global workspace theory of consciousness.